AMELIORATING EFFECTS OF GARLIC OIL AGAINST MOSQUITO COIL SMOKE INDUCED HISTOPATHOLOGICAL CHANGES IN RAT KIDNEY - ASHA AGARWAL; ANUJ KUMAR YADAV; RAJNI SINGH (International Journal of Pharma and Bio Sciences, 2013)
Present study was undertaken to evaluate the effect of garlic oil against mosquito coil smoke induced histopathological changes in kidney of the albino rat. Rats were exposed to one mosquito coil smoke (Baygon brand) for 8 hours (10 AM to 6 PM) daily for 28 days, Histopathological study reveals a remarkable damage to kidney tissue after inhalation of mosquito coil smoke. After supplementation of garlic oil (0.1 ml/100 g. b.wt) histopathological alterations have been mitigated in comparison to mosquito coil smoke exposed rats.